Exploring the role of natural resources, natural gas and oil production for economic growth of China. (December 2021) - Cui, Lianbiao; Weng, Shimei; Kirikkaleli, Dervis; Bashir, Muhammad Adnan; Rjoub, Husam; Zhou, Yuanxiang
Abstract: Economic growth and natural resources commodity prices are the variables greatly influenced by events such as the Gulf war, the Asian financial crisis, the global financial crisis, and the recent COVID-19 pandemic. The on-hand research fills the research gap by investigating the role of natural resources, natural gas and oil production for pre and post COVID-19 periods. The authors employ the Wavelet power spectrum and Wavelet coherence approaches to trace the volatility for natural resources commodity prices and establish a correlation between each variable and economic growth. The empirical findings suggest high fluctuations in the natural resources such as total natural resources, natural gas resources and oil rent for the stated period. This study found a bidirectional causal association between economic performance, total natural resources, natural gas resources and oil rent. The current research guides relevant policy implications to capture the volatile nature of resources commodity prices and to prescribe relevant policy implications in this regard. Highlights: Volatility of natural resource commodities and economic growth is examined. The wavelet power spectrum and coherence approaches are employed on time series. Natural gas, and oil rents show high fluctuations during studied period. Bidirectional causal link exists among GDP and natural resources commodity price. Novel findings and implications are drawn for post-COVID era.